A Timeless God? A Rejoinder to van Holten and Walton. (9th February 2020) - Swinton, John
Abstract : In this article John Swinton responds to the arguments detailed by Wilko van Holten2 and Martin Walton3 regarding the theology of the "Timelessness of God" and its relationship to disability and dementia (see 'A Critical Appraisal of John Swinton's Theology of Time and Memory' https://doi.org/10.1558/hscc.40137). Swinton acknowledges the value of van Holten and Walton's critique but points out that, by ignoring the genre of his work – pastoral theology – they have misunderstood critical aspects and failed to acknowledge important issues around the relationship between concepts and practice. The Response acknowledges that the argument for the timelessness of God is complex and problematic but argues that reflection on this requires practical exploration as well as theoretical conjecture. Swinton offers insights into how the reflection on the nature of God's involvement with time, properly construed, can throw important practical and theological light on to the lives of people with dementia and people with brain injuries.